Dynamics of agonist-evoked opioid receptor activation revealed by FRET- and BRET-based opioid receptor conformation sensors - Sina B. Kirchhofer; Claudia Kurz; Lorenz Geier; Anna-Lena Krett; Cornelius Krasel; Moritz Bünemann (Communications Biology)
Abstract The opioid receptor family, particularly the µ opioid receptor, are the main drug targets in the management of severe pain. However, their pain-relieving effects are often accompanied by severe adverse effects, underlining the necessity for extensive research on this receptor family. Opioids, the agonists targeting these receptors, differ in their chemical structure and also in their mode of action in different aspects of signaling. Here we introduce novel tools that facilitate the analysis of this receptor family, by the development of FRET- and BRET-based receptor conformation sensors. With these sensors we were able to characterize especially the µ opioid receptor in more detail and reveal a strongly agonist-dependent activation kinetics for this receptor. Moreover, our sensors offer an assay independent from other signaling pathways, thereby minimizing the potential for interfering influences or biases within the system.